2013
DOI: 10.1182/blood-2012-09-459289
|View full text |Cite
|
Sign up to set email alerts
|

A functional BCR in human IgA and IgM plasma cells

Abstract: Key Points IgA and IgM human plasma cells express a functional BCR on their cell surface and can therefore respond to antigenic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 20 publications
9
114
0
2
Order By: Relevance
“…Under these conditions, a significant fraction of the cells differentiated within 6 days into Ig-secreting CD138 + plasma cells [20,41,42]. B-cell maturation was followed by monitoring CD138 expression and icIgM ( Fig.…”
Section: Cxcr7 Is Differentially Expressed On Memory B Cells and Plasmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, a significant fraction of the cells differentiated within 6 days into Ig-secreting CD138 + plasma cells [20,41,42]. B-cell maturation was followed by monitoring CD138 expression and icIgM ( Fig.…”
Section: Cxcr7 Is Differentially Expressed On Memory B Cells and Plasmentioning
confidence: 99%
“…The rare peripheral blood plasma cells are characterized by high expression of CD27 and CD38, Ig secretion, and an increasing presence of CD138 [17]. Isolated plasma cells die within 3 days by apoptosis, but using BM-derived stromal cells as feeder cells remarkably improves plasma cell survival [18][19][20]. In agreement with this in vitro observation, it was shown that in vivo plasma cells, which express VLA-4 and CXCR4, in the BM colocalize with stromal cells expressing VCAM-1 and CXCL12 and may require additional survival factors [17,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar observation was previously reported for antibody-secreting cells in the human gut 8 and for plasma cells. 9 To further examine surface IgA on LLPCs, we turned to a mucosal disease that affects nearly all children, namely, rotavirus. During the first years of life, nearly all children will experience a rotavirus infection at least once.…”
Section: Resultsmentioning
confidence: 99%
“…IgA is not an inflammatory cytokine, but it plays an important role in intestinal mucosal immunity system by mediating humoral immunity. IgA is regulated by the nervous system, endocrine system and immune system, but IgA is released by plasma cells and has a vital role in intestinal mucosa immunity (Brandtzaeg, 2010;Pinto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%